Correlation Between Infant and Young Child Feeding Practices and Anthropometric Measurements in Children Less Than 2 Years in A Tertiary Care Centre In Kolar – an Observational Study. - Shankar, Vishaka; .J, Krishnappa (Journal of Neonatal Surgery, 2025)
Introduction: Under-nutrition is estimated to be associated with 2.7 million child deaths annually or 45% of all child deaths. Infant and young child feeding is a key area to improve child survival and promote healthy growth and development. Methodology: This study was conducted in RLJH hospital, Pediatric OPD. The study was started after obtaining ethical clearance from the institutional ethical committee as well as consents from the parents. All children satisfying inclusion and exclusion criteria were included for the study. IYCF Questionnaire was used to elicit the infant feeding practices and was correlated with the Anthropometric measurements. Results: The study shows that there are numerous feeding practices practiced in rural India which has impact on anthropometry. The practice which has a positive impact needs to be encouraged. In the study practice of Exclusive breast feeding for 6 months, initiating complementary feeding with locally available foods, no pre-lacteal feeds, introduction of fruits, vegetables, not introducing sugars and sweeteners till two years are good practices and need to be encouraged. The practices that need to discouraged are usage of feeding bottles, usage of formula feeds and not introducing eggs and meat till one year of age. Although cultural practices have an influence on feeding practices only positive ones need to be followed. In the study it was seen that only weight for age was majorly affected compared to other anthropometric measurements. This shows acute nutritional deficiency is more common rather than chronicity. The inter-current illnesses might also be a cause for this rather than feeding practice alone. Conclusion: The various feeding practices that are followed across India varies from Place to Place and Home to Home. Education alone can bring about changes in feeding practices